Efficiency of application of innovative marketing technologies. - Beyzhanova Ilesbekov, A. A. T. D. (Journal of Economic Research & Business Administration, 2016)
Today the necessity of innovative methods and techniques for Kazakhstan’s economics is an actual problem. The local companies have to implement and develop constant and innovative marketing technologies in order to succeed on the highly competitive market and take an independent stand in it. The innovative marketing technologies are the most effective concept or course of the marketing due to the renewal of the market with plenty of products. The innovative marketing technologies are innovative management techniques applied by enterpriser in defining and studying the demand, planning the manufacture, realization of the services and products. By using new techniques, we can perform market research efficiently and quickly, reduce the number of employees in the marketing, in general, to optimize the whole process.